Uma análise do efeito dos gastos públicos estaduais em segurança pública, assistência social e educação sobre a criminalidade no Ceará para o período de 2010 a 2013 - Amaral, Joafran Eufrasino do (2015)
Crime is a major problem faced by Brazil, directly affecting the population and demanding from the rulers a compelling performance. Aware of the problem, in order to identify the determinants of crime, it is observed that some authors have studied the impact of public expenditures on crime reduction. From this perspective, and based on the economic theory of crime, this work proposes to bring a further contribution to the subject, focusing on crime in the State of Ceará. After a brief theoretical review of crime literature, an empirical study using monthly data for lethal crimes (homicides), violence against property (thefts) and burglaries, looking check is performed, from the use of series time, the impact of state public spending on public safety, education and welfare in the three types of crime for the period 2010-2013. Results were contradictory to the government spending on public safety, which suggests a possible problem of causality reverse or that such expenditures are not well allocated. In contrast, the estimates reached showed that spending on education and social assistance, taken together, were negative and significant for lethal crimes, indicating that the increase in state spending on education and social assistance is effective to reduce the number of homicides.